HEROIC JOURNEY OF KATNISS EVERDEEN IN SUZANNE COLLINS' NOVEL CATCHING FIRE - Fakhruddin, Rohmat Anang (Balai Bahasa Jawa Timur, 2019)
This research aims to reveal the journey of Katniss Everdeen by using monomyth cycle in Suzanne Collins? novel Catching Fire (2009). This research used the literary criticism that employs the monomyth cycle of Joseph Campbell. The monomyth theory was used to explore Katniss? heroic journey within the novel Catching Fire. All data were classified into the following stages of monomyth cycle: departure, initiation, and return. Each stage represented the development of Katniss?s traits during her journey. From the analysis, it was discovered that Katniss began her journey by adapting herself in Victor?s Village after winning the 74th Hunger Games. She began her journey after President Snow provided her a challenge to convince him to reduce the uprising acts in each District. She refused to return home since she must rescue Peeta. Therefore, this paper concludes that this novel can be a continuity step of Katniss? Journey for transforming herself to be a heroine at the end of her Journey.